2013
DOI: 10.1128/jcm.02103-12
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of the Staphylococcus QuickFISH BC Test with the Tube Coagulase Test Performed on Positive Blood Cultures for Evaluation and Application in a Clinical Routine Setting

Abstract: bMany studies demonstrate that delayed proper therapy in bloodstream infections caused by Staphylococcus aureus increases the mortality rate, emphasizing the need to shorten the turnaround time for positive blood cultures. Different techniques are currently available, from phenotypic methods to more complex tests such as matrix-assisted laser desorption ionization-time of flight mass spectrometry (MALDI-TOF), real-time PCR (RT-PCR), and fluorescence in situ hybridization using peptide nucleic acid probes (PNA … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

2
24
0

Year Published

2013
2013
2016
2016

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 34 publications
(26 citation statements)
references
References 20 publications
2
24
0
Order By: Relevance
“…The Staphylococcus QuickFISH assay was previously shown to be 97.1% to 99.0% sensitive and 89.5% to 100% specific for the detection of staphylococci (15,16). More recently, the Enterococcus QuickFISH assay was shown to be 97% sensitive for the detection of non-E. faecalis enterococci (38).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The Staphylococcus QuickFISH assay was previously shown to be 97.1% to 99.0% sensitive and 89.5% to 100% specific for the detection of staphylococci (15,16). More recently, the Enterococcus QuickFISH assay was shown to be 97% sensitive for the detection of non-E. faecalis enterococci (38).…”
Section: Discussionmentioning
confidence: 99%
“…A number of different assays have been developed, each capable of detecting up to a maximum of 3 different species per assay. More recently, this method has been modified to incorporate a self-reporting probe design (QuickFISH), thereby eliminating the washing step and reducing the assay time to less than 30 min (15,16). The Verigene Blood Culture Gram-Positive (BC-GP) test uses array-based nanoparticle technology capable of detecting 12 different Grampositive organisms from positive blood cultures in a single assay.…”
mentioning
confidence: 99%
“…Phenotypic methods include a coagulase tube test for staphylococci, biochemical arrays in automated identification systems, and most recently, matrix-assisted laser desorption ionization-time of flight mass spectrometry (MALDI-TOF MS) (4,5). Genotypic identification methods include fluorescence in situ hybridization (FISH) with peptide nucleic acid (PNA) probes for a limited number of species and several commercially available multiplex nucleic acid amplification tests (NAATs) for a broad range of species recovered from blood cultures (3,(5)(6)(7)(8). With the existing blood culture systems, the time to positive result typically ranges from 1 to 3 days, and an additional 1 to 2 days is needed for species identification with conventional methods, although MALDI-TOF MS and genotypic methods have shortened this time to hours instead of days.…”
mentioning
confidence: 99%
“…They also reported that the Staphylococcus QFISH assay turnaround time was Ͻ30 min and the hands-on time was Ͻ5 min. Likewise, Carretto et al (15) reported 100% sensitivity and specificity for S. aureus detection in their single-center evaluation, with minimal impact with respect to modifying laboratory workflow to accommodate testing. Compared to FOX testing, the mecAX test had two false-negative and one atypical, weak, green, and false-positive fluorescent result (sensitivity and specificity, 99.1 and 99.6%, respectively; Table 2).…”
Section: Discussionmentioning
confidence: 99%